2018
DOI: 10.3889/oamjms.2018.435
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Purple Sweet Potato Balinese Cultivar in Wistar Rats With Ischemic Stroke

Abstract: BACKGROUND:Purple sweet potato (Ipomoea Batatas L.) is one of the sources for anthocyanin, which promotes the health through antioxidant, anti-inflammatory, anti-cancer, neuroprotection, and anti-apoptosis activities. Oxidative stress has been shown to be the cause of apoptosis in ischemic stroke.AIM:The objective of this research was to delineate the pleiotropic effects of anthocyanin for neuroprotection during an acute stroke event.METHODS:Anthocyanin was extracted from Balinese cultivar of purple sweet pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Both models of ischemia induction (global and focal) were applied in studies on the effects of ACN administration. Some studies reported their beneficial effect when administered before stroke induction [82,180,181,182,183,184], others after the stroke induction [165,185,186], while a third set of studies monitored the effects of ACN administration before and after stroke induction [81,187,188,189].…”
Section: Evidence For Anthocyanins’ Effects In the Prevention And mentioning
confidence: 99%
See 4 more Smart Citations
“…Both models of ischemia induction (global and focal) were applied in studies on the effects of ACN administration. Some studies reported their beneficial effect when administered before stroke induction [82,180,181,182,183,184], others after the stroke induction [165,185,186], while a third set of studies monitored the effects of ACN administration before and after stroke induction [81,187,188,189].…”
Section: Evidence For Anthocyanins’ Effects In the Prevention And mentioning
confidence: 99%
“…In experimental models the brain infarct volume and the apoptotic neurons provoked by induced stroke followed by reperfusion could be reduced by previous administration of ACNs [183]. Studies regarding the effect of pre-administration of ACNs on stroke used purified ACNs [82,181,182] or even encapsulated ACNs available on the market [183] (Table 4) with the aim to elucidate the molecular mechanisms by which ACNs act (see Section 4). Two modalities of stroke induction were applied, most often used is MCA occlusion model of focal ischemia [82,180,181,182,183] and only a single study used bilateral common carotid artery occlusion (BCCAO), which is a model of global ischemia [184], while various ways to administer ACNs are applied (Table 4).…”
Section: Evidence For Anthocyanins’ Effects In the Prevention And mentioning
confidence: 99%
See 3 more Smart Citations